(3ShGO GdfGXQ hTbGFb GdQhV GdfGXQs - (3YdGAGdOjf Ydj Hf eMeO Hf Ydj Hf YHO Gddg Hf CHi GdaJM GdcfGfi GdYSbdGfis; (3SdjeGf Hf YHO Gdbhj Hf GdcQje GdWhaj GdnqUrQnUQj, CHh GdQHjY, fLe GdOjf,J (B716 (3g` s ((3MajOI ef GHfI GdeDda YGFTI HfJ CMeO Hf EHQGgje Hf fUQGddg GdYSbdGfi s)
(3ChdgG (B:s
(3Ce HYO ajbhd CMeO Hf GHQGgje GdYSbdGfi s
(3BNQgG (B:s
(3ai GdUfa GdKGdK hgh GdJQLjM e LgI GdbQGFf s
(3GdQhVI ai GdCUhd ehab GdOjf Hf bPGeI GdebOSi GdMfHdi cTa GdXfhf (B1 (3U (B924s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3CUhd Gdabgs